2015
DOI: 10.1155/2015/593196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Auricular Acupressure on Uremic Pruritus in Patients Receiving Hemodialysis Treatment: A Randomized Controlled Trial

Abstract: Background. Uremic pruritus (UP) is a common symptom in patients undergoing maintenance hemodialysis for end-stage renal disease (ESRD). Objective. To determine the clinical efficacy of auricular acupressure therapy on pruritus in hemodialysis patients and to explore possible underlying mechanisms. Methods. Patients receiving maintenance hemodialysis at a referral medical center were recruited and assigned to intervention (n = 32) and control (n = 30) groups. The intervention group underwent auricular acupress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 20 publications
2
35
0
5
Order By: Relevance
“…Moreover [28] reported another regimen for duration of hemodialysis session as where high percentage of hemodialysis patients spend 1.5-2.75 hours six times per week. Another study done by [29] who reported that all participants enrolled in their study were undergoing hemodialysis and spent four hours for three times per week. In relation to frequency of hemodialysis session per week the current study finding reported that approximately all of the study participants adhere to hemodialysis session three times per week.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover [28] reported another regimen for duration of hemodialysis session as where high percentage of hemodialysis patients spend 1.5-2.75 hours six times per week. Another study done by [29] who reported that all participants enrolled in their study were undergoing hemodialysis and spent four hours for three times per week. In relation to frequency of hemodialysis session per week the current study finding reported that approximately all of the study participants adhere to hemodialysis session three times per week.…”
Section: Discussionmentioning
confidence: 99%
“…Auricular acupressure may be beneficial in uraemic pruritus as reported in an unblinded, placebo-controlled trial. 281 Two uncontrolled studies suggest the benefits of aromatherapy in uraemic pruritus. 282,283 Treatments in other uncontrolled studies that may show benefit in uraemic pruritus include Sericin cream, derived from silkworms, 284 topical turmeric 285 and oral omega-3 fatty acid supplements.…”
Section: Recommendationsmentioning
confidence: 99%
“…Acupressure combines massage and pressure to specific points, along a defined meridian, similar to those used for acupuncture. Auricular acupressure may be beneficial in uraemic pruritus as reported in an unblinded, placebo‐controlled trial …”
Section: Treatment Of Generalized Pruritus Of Unknown Originmentioning
confidence: 96%